The Golden Bough: A Study in Magic and Religion - Frazer, James George (Wordsworth Editions Ltd, 1993)
This volume is the author's own abridgment of his great work. It is remarkable for its vast assembly of facts and its charm of presentation,it offers the thesis that man progresses from magic through religious belief to scientific thought.
Keywords: Religion-Magic-Non fiction